Superior gelatine company - Ancheta, Fructuoso C.; Corpus, Llewelyn F.; Hsien, Alexander (Quezon City College of Engineering, 1968)
Capacity: 351,000 lbs. edible gelatine/year -- Fixed capital investment: 822,250 -- Operating cost at maximum production: 110,239 -- Sales at maximum production: 144,586 -- Pay-out time: 23.6 years -- Break-even point: 180,000 lbs. edible gelatine/year -- Plant location: Pasig, Rizal
Typescript.
Submitted in partial fulfillment of the requirements in ChE 62.
Keywords: Factories -- Design and construction; Gelatin